Early Phase I Study of a (99m)Tc-Labeled Anti–Programmed Death Ligand-1 (PD-L1) Single-Domain Antibody in SPECT/CT Assessment of PD-L1 Expression in Non–Small Cell Lung Cancer - Xing, Yan (J Nucl Med, 2019)
Immunotherapy with checkpoint inhibitor programmed cell death 1 (PD-1)/programmed death ligand-1 (PD-L1) antibodies demonstrates improvements in treatment of advanced non–small cell lung cancer. Treatment stratification depends on immunohistochemical PD-L1 measurement of biopsy material, an invasive method that does not account for spatiotemporal heterogeneity. Using a single-domain antibody, NM-01, against PD-L1, radiolabeled site-specifically with (99m)Tc for SPECT imaging, we aimed to assess the safety, radiation dosimetry, and imaging characteristics of this radiopharmaceutical and correlate tumor uptake with PD-L1 immunohistochemistry results. Methods: Sixteen patients (mean age, 61.7 y; 11 men) with non–small cell lung cancer were recruited. Primary tumor PD-L1 expression was measured by immunohistochemistry. NM-01 was radiolabeled with [(99m)Tc(OH(2))(3)(CO)(3)](+) complex binding to its C-terminal hexahistidine tag. Administered activity was 3.8–10.4 MBq/kg, corresponding to 100 μg or 400 μg of NM-01. Whole-body planar and thoracic SPECT/CT scans were obtained at 1 and 2 h after injection in all patients, and 5 patients underwent additional imaging at 10 min, 3 h, and 24 h for radiation dosimetry calculations. All patients were monitored for adverse events. Results: No drug-related adverse events occurred in this study. The mean effective dose was 8.84 × 10(−3) ± 9.33 × 10(−4) mSv/MBq (3.59 ± 0.74 mSv per patient). Tracer uptake was observed in the kidneys, spleen, liver, and bone marrow. SPECT primary tumor–to–blood-pool ratios (T:BP) varied from 1.24 to 2.3 (mean, 1.79) at 1 h and 1.24 to 3.53 (mean, 2.22) at 2 h (P = 0.005). Two-hour primary T:BP ratios correlated with PD-L1 immunohistochemistry results (r = 0.68, P = 0.014). Two-hour T:BP was lower in tumors with ≤1% PD-L1 expression (1.89 vs. 2.49, P = 0.048). Nodal and bone metastases showed tracer uptake. Heterogeneity (>20%) between primary tumor and nodal T:BP was present in 4 of 13 patients. Conclusion: This first-in-human study demonstrates that (99m)Tc-labeled anti–PD-L1-single-domain antibody SPECT/CT imaging is safe and associated with acceptable dosimetry. Tumor uptake is readily visible against background tissues, particularly at 2 h when the T:BP ratio correlates with PD-L1 immunohistochemistry results.